2017
DOI: 10.1111/bjd.15907
|View full text |Cite
|
Sign up to set email alerts
|

Adipochemokines induced by ultraviolet irradiation contribute to impaired fat metabolism in subcutaneous fat cells

Abstract: These UV-induced adipochemokines may be implicated in the reduction of lipogenesis in SC fat, leading to impairment of fat homeostasis and associated comorbidities such as obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 30 publications
3
22
0
Order By: Relevance
“…However, how these factors could influence SC fat activity still remained unclear. In their current paper, Kim et al . have shown for the first time that adipocytes treated with UVB‐irradiated keratinocytes and fibroblasts produce specific adipochemokines, including C–X–C chemokines such as ENA‐78, and C–C chemokines such as MIP‐3α and RANTES, which impair triglyceride synthesis via downregulation of lipogenic enzymes.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…However, how these factors could influence SC fat activity still remained unclear. In their current paper, Kim et al . have shown for the first time that adipocytes treated with UVB‐irradiated keratinocytes and fibroblasts produce specific adipochemokines, including C–X–C chemokines such as ENA‐78, and C–C chemokines such as MIP‐3α and RANTES, which impair triglyceride synthesis via downregulation of lipogenic enzymes.…”
mentioning
confidence: 83%
“…A fascinating and unexpected link between ultraviolet (UV)B and adipose tissue has been proposed by the pioneering original article of Kim et al ., published in the current issue of the BJD . It is well established that adipose tissue is not a mere inert fat‐storage facility, but is an endocrine organ secreting multiple mediators, named ‘adipokines’; furthermore, these adipokines are able to contribute to systemic inflammation .…”
mentioning
confidence: 99%
“…Clinical research has shown that the expression levels of CCL5 and CCR5 were increased in the subcutaneous adipose tissue of obese individuals in comparison with those in the lean population, which could be reduced back to the normal levels through physical exercise (Baturcam et al, 2014). One study (Kim et al, 2018) reported that ultraviolet irradiation of human sun-protected subcutaneous fat in vitro could induce CXCL5 and CCL5 production; CCL5 treatment dose-dependently reduced triglyceride (TG) content and downregulated the expressions of acetyl CoA carboxylase (ACC), fatty acid synthase (FAS), stearoyl CoA desaturase (SCD), and sterol regulatory element-binding protein-1(SREBP-1) in human adipocytes. The changes could be reversed when the CCL5 receptor, the CCR5 gene, is deleted, suggesting that CCL5 impairs the synthesis of TG by reducing the expression of SREBP-1 and lipogenic enzymes through binding to its receptor, CCR5.…”
Section: Dyslipidemiamentioning
confidence: 99%
“…Moreover, elevated fat mass despite a normal BMI could also perpetuate a chronic inflammatory state [8]. However, an increase in subcutaneous adiposity, in contrast to an increase in visceral fat, may prevent Mets and systemic inflammation [12]. Indeed, subcutaneous adipocytes treated with UVBirradiated keratinocytes and fibroblasts may induce chemokines or cytokines impairing fat homeostasis, exerting the secretion of pro-inflammatory adipokines and exacerbating associated comorbidities such as obesity [12,13].…”
Section: The Crucial Role Of Adipose Tissue Adipocytokines and Inflamentioning
confidence: 99%
“…However, an increase in subcutaneous adiposity, in contrast to an increase in visceral fat, may prevent Mets and systemic inflammation [12]. Indeed, subcutaneous adipocytes treated with UVBirradiated keratinocytes and fibroblasts may induce chemokines or cytokines impairing fat homeostasis, exerting the secretion of pro-inflammatory adipokines and exacerbating associated comorbidities such as obesity [12,13]. Further studies are needed to clarify the role of subcutaneous adipose tissue in psoriatic inflammation.…”
Section: The Crucial Role Of Adipose Tissue Adipocytokines and Inflamentioning
confidence: 99%